Local characterization of vegetation through growth forms: Mediterranean Quercus ilex coppice as an example - Floret, C; Galan, N J; Floc'h, E; Orshan, G; Romane, F (Plant Ecology, 1987)
Growth forms are considered from two viewpoints: a descriptive and a functional one. Mono-character growth forms and their biological spectra were used to test whether they can characterize certain underlying processes in Quercus ilex coppice in southern France. Correspondence analysis of 35 mono-character growth forms of 203 described taxa shows that location of renewal buds is a good integrating indicator of plant adaptations to the environment. Two of these characters (renewal bud location, Le. Raunkiaer's main life forms, and leaf consistency) appear to vary significantly along a gradient of increasing environmental constraints, especially climatic ones.
Keywords: coppice; growth form; Life form; Mediterranean climate; Quercus ilex L; Southern France